Management of HIV/AIDS Opportunistic Infections by Using Medicinal Plants: A Case Study from Njeru Sub-County, Buikwe District, Uganda - Shehu , Mustapha W.; Bello , Idris; Abdulkadir , Nafi’u; Shehu , Abdulazeez; Jamil , Ssenku Ediris; Waziri , Sadiya A. (Current Progress in Medicine and Medical Research Vol. 6, 2023)
This chapter focused on documentation of the plants used in the management of HIV/AIDS opportunistic infections before they are lost through degradation of their habitat and death of the elderly people who have the knowledge about them and also their effectiveness in the management of the opportunistic diseases was assessed. Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) is a major cause of premature death and imposes a large disease burden around the world. Most HIV/AIDS patients are at risk for developing bacterial and fungal opportunistic infections as a result of immune suppression. However, there is insufficient evidence to support the growing use of medicinal plants as an additional and alternative therapeutic approach to combat HIV/AIDS opportunistic infections. The study was conducted in the Njeru sub-county, Buikwe District. The study focused on the utilization of medicinal plants used in the management of HIV/AIDS opportunistic infections. A total of 52 medicinal plant species belonging to forty-nine (49) genera and thirty-one (31) families were identified to be used by traditional medicinal practitioners (TMPs) in the management of HIV/AIDS opportunistic infections. Most of these plants were found to belong to the families; Lamiaceae, Moraceae, Leguminosae, and Verbenaceae. Most of the plant species identified were known to manage skin infections, chronic cough, tuberculosis, stomach infections, diarrhea, herpes zoster, and Warts. Although the herbs were used to treat a variety of illnesses, warts, herpes zoster, chronic cough, stomach infections, and chronic cough were the most frequently reported. Traditional medical practitioners (TMPs) primarily drank decoctions as a method of application.